WAR BONDS AS A FINANCIAL INSTRUMENT FOR LOCAL GOVERNMENTS - Краківський Юрій C. (Journal of Strategic Economic Research, 2025)
A full-scale military invasion significantly changed the financial system of Ukraine. The economy was supported by international aid and the government’s debt policy. Of particular importance during this period were domestic government bonds (DGB), which were called war bonds during martial law, and which raised UAH 1,311 billion. The purpose of the study was to investigate the state of circulation of domestic government bonds belonging to territorial communities and free balances of budget funds of local communities. The study applied methods of comparative, structural, economic, and statistical analysis, compared indicators in the war and pre-war period of free budget balances at the beginning, calculated the share of DGBs belonging to territorial communities, which was only 0.04%. It was established that half of the free budget balances of local communities belonged to front-line territories. Although the legislation of Ukraine restricts the use of the free balance of budget funds, it is allowed to use in particular to support the defence forces, create conditions for the treatment, restoration, and rehabilitation of persons affected by the armed aggression of the Russian Federation against Ukraine; for measures and work on territorial defence and mobilisation training; design, construction, repair of civil protection structures (storage facilities, anti-radiation shelters), dual-use structures and arrangement of premises that are planned to be used to shelter the population; construction of fortifications, purchase of medicines and dressings for other purposes. The growth rate of free budget balances of local communities during the war period indicates inefficient use of financial resources. In the pre-war period, local communities actively used deposits to place free budget balances. Despite the growth of free budget balances, the volume of war bonds owned by territorial communities is decreasing. The possibility of placing free budget balances on deposits is limited in wartime by the need to purchase government securities in the amount of at least 50% of the funds placed on deposits. The study is of practical importance for local self-government bodies and state institutions, contributing to decision-making on the circulation of DGBs and the management of free budget balances. In the scientific sphere, it serves as a source of information for investigating the debt policy of the state.